2004
DOI: 10.3818/jrp.6.1.2004.93
|View full text |Cite
|
Sign up to set email alerts
|

The Reentry Court Initiative: Court-Based Strategies for Managing Released Prisoners

Abstract: In response to the growing need to effectively manage the large numbers of released prisoners returning into the community, the Office of Justice Programs launched the Reentry Court Initiative (RCI). Nine sites were identified and charged with developing strategies to improve the tracking and supervision of offenders upon release and providing the services necessary to help offenders reconnect with their families and the community. The current article describes the RCI programs. Telephone interviews were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…117 Alternatively, a Reentry Court can be a stand-alone court where a retired judge, magistrate, administrative judge, or another judicial officer maintains an exclusive docket of reentry cases. 118 One example is the Los Angeles County Women's Reentry Court, operated under the jurisdiction of California's Department of Corrections. 119 This Reentry Court is a voluntary treatment diversion program for women who are already under parole, and now face a new, nonviolent criminal offense.…”
Section: Why Should States Adopt a Reentry Court Model? A Reentrmentioning
confidence: 99%
“…117 Alternatively, a Reentry Court can be a stand-alone court where a retired judge, magistrate, administrative judge, or another judicial officer maintains an exclusive docket of reentry cases. 118 One example is the Los Angeles County Women's Reentry Court, operated under the jurisdiction of California's Department of Corrections. 119 This Reentry Court is a voluntary treatment diversion program for women who are already under parole, and now face a new, nonviolent criminal offense.…”
Section: Why Should States Adopt a Reentry Court Model? A Reentrmentioning
confidence: 99%
“…While no known empirical research has investigated the reentry court judge in light of a strengths-based perspective, some research has begun to investigate reentry courts' effects on recidivism (Spelman, 2003;Farole, 2003;Hamilton, 2010;Taylor, in press) and the associated processes (Lindquist, Hardison, & Lattimore, 2004;Taylor, 2010). A process evaluation of one of the first large-scale reentry court projects, titled the Reentry Court Initiative (RCI), indicated that the nature of the interaction between judge and participant was crucial.…”
Section: The Limited Research On the Role Of The Judge In Reentry Courtsmentioning
confidence: 97%
“…Even in the first iteration of reentry courts under OJP's Reentry Courts Initiative, many programs operated on a very small scale (Lindquist, Hardison, and Lattimore 2004 (Hogan 2011, tbl. 8).…”
Section: Limited Benefit: the Challenge Of Taking Change To Scalementioning
confidence: 99%